Determinación del nivel de cromo hexavalente en los pozos tubulares y efluentes de drenaje de las lagunas de oxidación, del distrito de moche, en el periodo enero - agosto del 2010 - Mozo Valdivieso, Ronal Fredi (2012)
This research was aimed at determining the level of hexavalent chromium (Cr6 + in mg / l) in the waters of three boreholes and two effluent drainage system adjacent to the oxidation ponds Sector America populated center San Borja Moche District between January and August 2010 and compare these levels with the maximum permissible limits (LMP) provided for in Regulation of Quality of Drinking Water D.S. N ° 031-2010-SA. These waters are used in agriculture and domestic use by the locals. Studies by the World Health Organization (WHO) and the investigation of Otiniano G, et al, 2007, p.4, establish that the prolonged ingestion of hexavalent chromium (Cr6+), mutagenic and carcinogenic effect on health. For the testing of the hypothesis of this research is not experimental trans type, we analyzed 40 samples, 8 replicas applied to 5 sampling stations. Spectroscopic laboratory reports of the Faculty of Chemical Engineering, National University of Trujillo, indicate the following concentrations: For P-I sampling station 0,163 mg/l, for sampling station P-II 0.0657 mg/l, for the season P-III sampling 0.00 mg/l, for F-I sampling station 0.3311mg/l for the sampling station F-II 0.3147mg/l. Levels except for the sampling station P-III, reported concentrations exceeding permissible limits of 0.05 mg/l for total chromium, according to the D.S. Nº 031-2010-SA. And the current national standard for liquid effluent discharge activities Mining and Metallurgical, D.S Nº 010-2010-MINAM